Making a Website Using Bootstrap for SMK Students in Sungai Raya Kepulauan District - Nella Yuniarni, Nella; Enda Esyudha P; M Azhar Irwansyah; Haried Novriando; Anggi Srimurdianti S; Fauzan Asrin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tanjungpura, 2023)
The problem that often arises in an educational institution such as a vocational school is the lack of complete digital literacy knowledge about web design and creation through training. So that students lack competency in designing and building a web technology. In fact, the training conducted is a way to increase the competency of SMK students and female students to be able to have expertise in building websites according to the needs of both static web needs and dynamic web needs. Website technology is a new way of facilitating the process of conveying information which is a logical consequence of the current developments in information and communication technology on the internet. In building a website there are many frameworks that can be used, one of which is bootstrap. Bootstrap is a free and open source CSS framework for designing websites and web applications. This framework contains HTML and CSS-based design templates for typography, forms, buttons, navigation, and other interface components, as well as optional JavaScript extensions.